2001
DOI: 10.1007/pl00007953
|View full text |Cite
|
Sign up to set email alerts
|

Stereochemical metabolism of styrene in volunteers

Abstract: Stereochemical metabolism of styrene in volunteersWenker, M.A.M.; Kezic, S.; Monster, A.C.; de Wolff, F.A. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Recently, we prepared a polyclonal antibody as an experimental tool to detect racemic SO modified proteins . The effort in the development of antibodies to selectively detect protein adducts modified by SO enantiomers was inspired by the findings of toxic effects of SO with enantiomeric differentiation. The availability of the antibodies would assist us to investigate the enantiomeric role of SO in styrene-mediated toxicity. A number of immunoassays developed for analysis of chiral drugs, such as propanolol, alprenolol, and pentobarbital, ractopamine, finrozole, and S-20499, have been reported.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we prepared a polyclonal antibody as an experimental tool to detect racemic SO modified proteins . The effort in the development of antibodies to selectively detect protein adducts modified by SO enantiomers was inspired by the findings of toxic effects of SO with enantiomeric differentiation. The availability of the antibodies would assist us to investigate the enantiomeric role of SO in styrene-mediated toxicity. A number of immunoassays developed for analysis of chiral drugs, such as propanolol, alprenolol, and pentobarbital, ractopamine, finrozole, and S-20499, have been reported.…”
Section: Resultsmentioning
confidence: 99%
“…Styrene oxide has one chiral center with two optical isomers as shown in Scheme . It was reported that the ( R )-styrene oxide ( R SO) was preferentially formed in mice, especially in the lung, whereas the ( S )-styrene oxide ( S SO) was preferentially generated in rats. In human volunteers, the cumulative excretion of the ( S ) - enantiomer of styrene glycol and mendelic acid were higher than the R form after exposure to styrene . In human liver microsomes, cytochrome P450-mediated styrene oxidation showed the production of more S SO relative to R SO .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Styrene‐derived glucuronide and sulfate conjugates can also be formed from other intermediate hydroxylated metabolites, such as styrene glycol (SG) and 1‐ and 2‐phenylethanol (PE). The urinary excretion of SG conjugates, as well as free and conjugated SG in blood, has recently been investigated in 20 healthy volunteers exposed to 360 mg/m 3 (84.7 ppm) sty‐rene for 1 h during physical exercise with the aim of studying the inter‐individual variability in the stereochemistry of styrene metabolism 18. SG excretion, determined after hydrolysis of urine and blood samples, accounted for about 1% of that of MA, where free SG in urine is less than 5% of the total SG content.…”
mentioning
confidence: 99%